In Silico Design of a Single Protein Molecular Photoreaction Center - Mishra, Nibedita; Mohapatra, Pranab K.; Raval, Mukesh K. (Micro and Nanosystems, 2020)
Background: Research on harvesting solar energy through an artificial photosynthetic device is gaining momentum in the present era. The device is a promising solution to the energy crisis by overcoming the crunch in fossil fuel and low efficiency of heat engine. Reports are available on design of isolated parts of the photosynthetic device, for example, only sensitizer or only redox unit containing metallo-peptides. Objective: An attempt has been made to design an in silico photoreaction center in a single chain protein matrix containing all the three basic units: sensitizer, electron donor, and acceptor mimicking the photosynthetic reaction center II. Methods: A single chain of a protein containing a closely packed transmembrane four-helix bundle (PDB ID 2bl2 A) is selected for the purpose. The protein is suitably mutated in silico to accommodate the basic elements of a reaction center: Mn-Ca binding site as water oxidizing moiety, Fe-binding site as quinine reducing moiety, and MgDPP as photosensitizer to achieve the desired function of photoredox reaction. Results: A photoelectron transport protein has been designed, which may incorporate into the bilayer membrane system. It has the potential to photo-oxidize water to oxygen on one side and reduce quinone on the other side of the membrane. The stability and transmembrane orientation of the molecular device in an artificial membrane system has been validated theoretically by molecular dynamics study. Conclusion: An attempt to incorporate in silico all the elements essential for a photoelectron transport device into a single chain transmembrane protein model is the first of its kind. Donor and acceptor moieties are separated on the inner and outer side of a membrane bilayer. These features make the model unique and novel. The design of the model is the first step towards the study of experimental viability of the model, which remains to be validated in future.
Keywords: photoredox reactions